2020
DOI: 10.1186/s13063-020-04360-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blogshots with plain language summaries of Cochrane systematic reviews: a qualitative study and randomized trial

Abstract: Background Cochrane, an organization dedicated to the production and dissemination of high-quality evidence on health, endeavors to reach consumers by developing appropriate summary formats of its systematic reviews. However, the optimal type of presentation of evidence to consumers is still unknown. Objective The aim of this study was to investigate consumer preferences for different summary formats of Cochrane systematic reviews (CSRs), using both qualitative and quantitative approaches. Methods Initially,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 26 publications
(26 reference statements)
1
25
0
1
Order By: Relevance
“…Many outcomes could be linked to aims of the Accessibility category. In their empirical studies, researchers investigated the readability of PLSs [ 6 , 13 , 15 , 21 , 22 , 28 , 43 – 48 ], participants’ enjoyment or preference of PLSs in general [ 10 , 11 , 39 , 49 ], participants’ satisfaction with text length [ 13 , 22 , 42 ] or participants’ judgment regarding the usability of the PLS [ 3 , 12 , 23 , 28 , 50 , 51 ]. To measure these outcomes, researchers, for example, computed readability indices, such as the Flesch reading ease score [ 13 , 44 , 43 , 47 , 48 ], or participants were asked whether information was easy to find in the PLS [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many outcomes could be linked to aims of the Accessibility category. In their empirical studies, researchers investigated the readability of PLSs [ 6 , 13 , 15 , 21 , 22 , 28 , 43 – 48 ], participants’ enjoyment or preference of PLSs in general [ 10 , 11 , 39 , 49 ], participants’ satisfaction with text length [ 13 , 22 , 42 ] or participants’ judgment regarding the usability of the PLS [ 3 , 12 , 23 , 28 , 50 , 51 ]. To measure these outcomes, researchers, for example, computed readability indices, such as the Flesch reading ease score [ 13 , 44 , 43 , 47 , 48 ], or participants were asked whether information was easy to find in the PLS [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…We identified 15 empirical articles on PLSs that evaluated one type of PLSs, for example by investigating how readers reacted to a certain PLS, or how easy they can be found. Researchers evaluated Cochrane PLS that address common health issues [ 11 , 57 ], summaries of studies from the Newcastle Cognitive Function after Stroke cohort [ 45 ], consumer summaries of Cochrane Musculoskeletal Reviews [ 23 ], lay summaries on how package sizes affect the consumption of food, alcohol and tobacco [ 28 ], lay summaries on open access journal articles [ 3 ], lay summaries of pragmatic pediatric clinical trials [ 19 ], lay summaries on HDBuzz, a knowledge translation website with a focus on research on Huntington’s disease [ 52 ], PLSs of clinical trials in general [ 21 , 93 , 94 ], PLSs of clinical trials in Japan [ 95 ] and PLSs posted as ‘eLife digests’ [ 8 , 66 ]. There was also one study that investigated how the commitment of volunteer PLS authors can be raised [ 96 ] and one study that developed and tested a PLS template in detail [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the highly respected and high-quality sources of information for both the doctors and the patients is summaries of evidence synthesis—scientific abstracts and plain language abstracts, respectively, such as those produced by Cochrane. We have previously shown that plain language summaries of Cochrane systematic reviews increase knowledge of patients about health issues that is comparable to infographics of the same abstract [ 1 ]. Shortened versions of plain language summaries of Cochrane systematic reviews in the form of single-slide brief and focused information (blogshots) seem to be even more effective than plain language summaries in terms of change in comprehension of health information among patients/consumers [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that plain language summaries of Cochrane systematic reviews increase knowledge of patients about health issues that is comparable to infographics of the same abstract [ 1 ]. Shortened versions of plain language summaries of Cochrane systematic reviews in the form of single-slide brief and focused information (blogshots) seem to be even more effective than plain language summaries in terms of change in comprehension of health information among patients/consumers [ 1 ].…”
Section: Introductionmentioning
confidence: 99%